Magnetic resonance imaging-guided brachytherapy for cervical cancer: initiating a program - Owrangi, Amir M.; Prisciandaro, Joann I.; Soliman, Abraam; Ravi, Ananth; Song, William Y. (Journal of Contemporary Brachytherapy, 2015)
Over the past decade, the application of magnetic resonance imaging (MRI) has increased, and there is growing evidence to suggest that improvements in accuracy of target delineation in MRI-guided brachytherapy may improve clinical outcomes in cervical cancer. To implement a high quality image guided brachytherapy program, a multidisciplinary team is required with appropriate expertise as well as an adequate patient load to ensure a sustainable program. It is imperative to know that the most important source of uncertainty in the treatment process is related to target delineation and therefore, the necessity of training and expertise as well as quality assurance should be emphasized. A short review of concepts and techniques that have been developed for implementation and/or improvement of workflow of a MRI-guided brachytherapy program are provided in this document, so that institutions can use and optimize some of them based on their resources to minimize their procedure times.